PENINGKATAN PEMAHAMAN MAKNA ESOTERIK SURGA DALAM TAFSÎR LATHÂʽIF AL-ISYÂRÂT DI MASJID AN-NUR, BABELAN BEKASI - Nur Rofiah; Yanti Cholidah; Nurbaiti Nurbaiti; Salman Faris; Fikri Hakim; Ahmad Zain Sarnoto (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The interpretation of the concept of heaven in the Qur'an which stops at a literal or exoteric dimension has basically narrowed the breadth of the meaning of the Qur'an, which in the end will give birth to an irresponsible reason to carry out jihad accompanied by acts of terror for the sake of get the pleasure of the angels who are prepared for the mujahid who struggles in the way of Allah SWT. This research is a qualitative research with literature study, the approach used is an esoteric approach in interpreting the verses of the Qur'an about heaven. This study concludes that, in his interpretation Al-Qusyairȋ classifies heaven into two categories, namely suspended heaven (muajjalah) and hastened heaven (mu'ajjalah). The suspended paradise (muajjalah), is heaven that will be obtained in the hereafter by going through a very long journey, is a form of elevation, and is a form of His generosity (jûdih) as a reward for those who are pious and do good deeds. The characteristics of this paradise are in the form of material meanings of dzahir as described in the verses of the Qur'an. And the hastened paradise (mu'ajjalah), is a paradise that can be obtained in the world by experts in essence and the magicians in the form of closeness (qûrbah) and is a veiling disclosure of various forms of occult secrets (kasyf al-ghithâ) which is interpreted with the essence of the nature of achievement (haqâiq al-wishâl) and closeness to Allah SWT as pleasure in carrying out obedience and peace of mind